The 8th habit: from effectiveness to greatness - Covey, Stephen R (Simon & Schuster UK New York, 2013)
In the 7 Habits series, international bestselling author Stephen R. Covey showed us how to become as effective as it is possible to be. In his long-awaited new book, THE 8th HABIT, he opens up an entirely new dimension of human potential, and shows us how to achieve greatness in any position and any venue. All of us, Covey says, have within us the means for greatness. To tap into it is a matter of finding the right balance of four human attributes: talent, need, conscience and passion. At the nexus of these four attributes is what Covey calls voice - the unique, personal significance we each possess. Covey exhorts us all to move beyond effectiveness into the realm of greatness - and he shows us how to do so, by engaging our strengths and locating our powerful, individual voices. Why do we need this new habit? Because we have entered a new era in human history. The world is a profoundly different place than when THE 7 HABITS OF HIGHLY EFFECTIVE PEOPLE was originally published in 1989. The challenges and complexity we face today are of a different order of magnitude. We enjoy far greater autonomy in all areas of our lives, and along with this freedom comes the expectation that we will manage ourselves, instead of being managed by others. At the same time, we struggle to feel engaged, fulfilled and passionate. Tapping into the higher reaches of human genius and motivation to find our voice requires a new mindset, a new skill-set, a new tool-set - in short, a whole new habit